Health care costs associated with Australian tertiary inflammatory bowel disease care. (3rd August 2017) - Jackson, Belinda; Con, Danny; Ma, Ronald; Gorelik, Alexandra; Liew, Danny; De Cruz, Peter
Abstract: Introduction: We aimed to describe the total costs of illness for IBD patients and compare the costs of patients with active disease to those with inactive disease. Materials and methods: Resource use for IBD management was itemized for attributable costs (AUD) among all IBD patients over a 12-month period at an Australian hospital. Results: One hundred and eighty-three patients were included (87 ulcerative colitis (UC); 93 Crohn's disease (CD); three IBD-unclassified). The median (IQR) annual overall cost was higher in the CD versus UC group (15, 648 versus 5017; p < .001). The difference in cost between CD and UC was influenced by the difference in outpatient costs for CD patients 9602 (4311–29, 805) versus 4867 (3220–7249), p < .001). The cost of treating patients with active disease was 3461 (1607–11, 771) and was higher in the CD versus the UC group (6098 (2168–16, 471) versus 1638 (1401–3767); p = .026) and was influenced by inpatient admissions. The cost of treating patients in remission was 2090 (1552–12, 954) and was higher in the CD versus the UC group [7977 (1579–14, 304) versus 1848 (1508–6601); p = .236]. Conclusions: There is a discrepancy in costs of inpatient versus outpatient IBD management and treating active disease compared with disease in remission. Proactive care may help prevent disease reaching a severity whereby reactive management of active disease is required.